2013
DOI: 10.1007/s10964-013-9973-x
|View full text |Cite
|
Sign up to set email alerts
|

Which Behavioral, Emotional and School Problems in Middle-Childhood Predict Early Sexual Behavior?

Abstract: Mental health and school adjustment problems are thought to distinguish early sexual behavior from normative timing (16–18 years), but little is known about how early sexual behavior originates from these problems in middle-childhood. Existing studies do not allow for co-occurring problems, differences in onset and persistence, and there is no information on middle-childhood school adjustment in relationship to early sexual activity. This study examined associations between several middle-childhood problems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 90 publications
(165 reference statements)
0
17
1
3
Order By: Relevance
“…Particularly if peer rejection engenders feelings of loneliness and social disconnectedness (Boivin, Hymel, & Bukowski, 1995), individuals who were rejected by peers during childhood may try to connect with others in any way possible, including through early sexual intercourse and multiple sexual partners. However, Parkes et al (2014) found that children whose mothers reported that they had more peer relationship problems at ages 6–8 and 10–11 years were less likely to have early sexual involvement (defined as adolescents’ reports of engaging in oral sex or sexual intercourse within the last year, reported at age 15). Therefore, it is possible that peer rejection during childhood may protect against risky sexual behavior if rejected children have less social interaction in general and therefore less opportunity to develop relationships that would lead to sexual behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Particularly if peer rejection engenders feelings of loneliness and social disconnectedness (Boivin, Hymel, & Bukowski, 1995), individuals who were rejected by peers during childhood may try to connect with others in any way possible, including through early sexual intercourse and multiple sexual partners. However, Parkes et al (2014) found that children whose mothers reported that they had more peer relationship problems at ages 6–8 and 10–11 years were less likely to have early sexual involvement (defined as adolescents’ reports of engaging in oral sex or sexual intercourse within the last year, reported at age 15). Therefore, it is possible that peer rejection during childhood may protect against risky sexual behavior if rejected children have less social interaction in general and therefore less opportunity to develop relationships that would lead to sexual behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Academic performance was assessed with the question, "What is your class rank this semester?" The response categories were 1 (top 5), 2 (6-10), 3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and 4 (over 21). Health status was based on self-rated health using five response categories.…”
Section: Control Variables (Wave 1 and Wave 2)mentioning
confidence: 99%
“…For example, problem behavior theory [14] argues problem behaviors tend to cluster; hence, early substance use is highly related to later risky behavior, including risky sexual behaviors [15][16]. Similarly, social control theory [17] argued a lack of social bond (e.g., low school commitment) "releases" an individual for deviance, including risky sexual behaviors [18]. Other factors simply provide opportunities for sexual practice and are related to risky sexual behaviors, such as those in a romantic relationship [15,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, approximately 1 in 5 youth experience some form of mental or behavioral health challenges (Kleintjes, Lund, & Flisher, ). Children who exhibit early externalizing behaviors are more likely to have increased rates of alcohol‐related problems, illicit drug use (Fergusson, Horwood, & Lynskey, ), and increased odds of engaging in risky behaviors such as sexual risk‐taking (Fergusson, Horwood, & Ridder, ; Fontaine et al, ; Parkes et al, ; Timmermans, van Lier, & Koot, ; Wu, Witkiewitz, McMahon, & Dodge, ). In addition, youth who exhibit destructive childhood behavioral patterns (e.g., lying, cheating, yelling, public disobedience, and physical violence; Frick, ) are more likely to have an elevated risk for experimenting with illicit substances as they enter adolescence and adulthood (Hopfer et al, ).…”
Section: Introductionmentioning
confidence: 99%